Asserting a scalar ordering: The non-temporal interpretation of mae - Tatsumi, Yuta (Proceedings of the Amsterdam Colloquium, 2017)
This paper argues that a non-temporal interpretation of mae ‘before’ in Japanese includes scalar ordering, but the scalar aspect of the non-temporal interpretation is neither an implicature nor a presupposition. The non-temporal mae ‘before’ asserts a scalar ordering of two propositions, with respect to an attitude holder’s belief about degrees of precision, instead of temporal precedence. It will also be argued that the non-temporal mae is syntactically different from the temporal one in that the former takes a VP as its complement.